ANALYSIS OF THE POSSIBILITIES OF IMPLEMENTING DIGITAL MONITORING TECHNOLOGIES INTO MUNICIPAL SOLID WASTE MANAGEMENT SYSTEMS OF COMMUNITIES OF POLTAVA REGION - BREDUN, VIKTOR; BREDUN, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
One of the urgent tasks facing rural communities in Poltava region is to improve waste management systems. Among the logistical aspects, the main ones are the structure of the road network and optimization of routes. In this regard, one of the ways to increase the efficiency of waste collection systems, as shown by European experience, is the introduction of operational route planning technologies based on digital waste accumulation monitoring systems such as the Internet of Things (IoT), RFID systems and mobile applications. This allows for dynamic route adjustment, which significantly increases the efficiency of waste management systems by optimizing logistics and involving citizens in active participation in waste management. However, due to a number of regional features, not all communities in Poltava region at this stage of their economic, infrastructural and demographic development have the opportunity to introduce digital technology in waste management systems. For individual communities, in addition to the issue of possibility, the issue of expediency of implementing such systems is also relevant. The main goal of the work is to study the directions and possibilities of adapting European experience to the conditions of Ukrainian communities. The work studies the experience of European municipalities in implementing digital technologies in solid waste management systems. The factors of feasibility and possibilities of implementing digital solutions in municipal waste management systems are determined. Based on the analysis of the current state of waste management systems of territorial communities of Poltava region, their typification was carried out and categories of communities were determined by the degree of readiness for the implementation of digital solutions. For each category of communities, recommendations are formulated for the integration of digital technologies into waste management systems. The results obtained substantiate the principles of modernization of the waste management system of territorial communities of Poltava region.